The Lithuanian version of the Attitudes Towards Suicide Questionnaire (ATTS) - Skruibis, Paulius; Gailienė, Danutė; Labanauskaitė, Lina (Psichologija, 2008)
Several psychological models explaining formation of attitudes towards suicide and their influence on suicidal behaviour have been developed recently. Reliable an valid instruments measuring attitudes towards suicide are needed to test these models. There are several well known questionnaires in this field: Suicide Opinion Questionnaire (SOQ; Domino et al., 1982), Suicide Attitude Questionnaire (SUIATT; Diekstra & Kerkhof, 1988). Both these questionnaires have methodological or practical disadvantages that were taken into account when developing a new instrument – Attitudes Towards Suicide Questionnaire (ATTS; Salander Renberg & Jacobsson, 1998).Objective: Lithuanian version of ATTS was created in 2001 and was used in a number of studines since then. Availability of large data pool (N = 1259) collected with Lithuanian version of ATTS has created a good opportunity for examining reliability and validity issues of the instrument, which is the aim of this study.Method: The data for the present study was taken from studies conducted in the framework of European multicenter research project SUPPORT. Sample consisted of 16 target groups that were studied with the Lithuanian version of ATTS: army conscripts (N = 368), army sergeants (N = 106), army officers (N = 44), medicine students (N = 103), students of priest seminaries (N = 68), catholic religion students (N = 63), psychology students (N = 137), members and mayors of Municipality Councils (N = 55), students of journalism (N = 43), journalists (N = 43), volunteers of psychological help-line (N = 43), suicide attempters (N = 40), personnel of emergency hospital (N = 39), homosexual and bisexual men (N = 30), alcohol dependant patients (N = 38), alcohol dependant patients undergoing Minnesota rehabilitation program (N = 39). A test-retest survey was performed in a sample of medicine students (N = 30) in order to evaluate temporal stability of ATTS Lithuanian version.Results: Confirmatory factor analysis (implemented through SEM) hasn’t confirmed the original ATTS factor model obtained by developers in Sweden. However, an exploratory factor analysis produced 5 factor model (explaining 53.5% of total variance), which is very similar at face value to other proposed ATTS factor models. Internal consistency of this model is satisfactory (Cronbach alpha – 0.68). Differences between attitudes of suicidal and non-suicidal individuals are regarded as support for criterion validity of the instrument. ICC coefficients from test-retest study are satisfactory (ranging from 0.62 to 0.87) for three ATTS factors. The remaining have demonstrated low testretest reliability (ICC coefficients are 0.48 and 0.59).Conclusions: psychometric properties of Lithuanian ATTS version were found to be satisfactory, although structural validity indicators were somewhat controversial and two factors have demonstrated low test-retest coefficients. Lithuanian ATTS version can be used for scientific research of attitudes towards suicide.
Keywords: attitudes towards suicide; ATTS; psychometric characteristics of the questionnaire